Mixed Convection over an Inclined Wavy Surface in a Nanofluid Saturated Non-Darcy Porous Medium with Radiation Effect - Darbhasayanam Srinivasacharya; Poshala Vijay Kumar (International Journal of Chemical Engineering)
The problem of mixed convection in a nanofluid along an inclined wavy surface embedded in a non-Darcy porous medium with radiation effect is analyzed. Coordinate transformation is employed to transform the complex wavy surface to a smooth surface. The governing equations are transformed into a set of ordinary differential equations using the appropriate similarity transformation and then solved using the successive linearization method. The present results are compared with previously published work and are found to be in very good agreement. The effect of pertinent parameters on the nondimensional velocity, temperature, nanoparticle volume fraction, heat, and nanoparticle mass transfer rates is studied and presented graphically.